EFEKTIVITAS STARTEGI KAMPANYE IKLAN EDUKASI BANK BCA "DON'T KNOW? KASIH NO!" TERHADAP MARAKNYA FENOMENA PHISHING DI MASYARAKAT - Anita Kusumawati; Agita Sekar Nahdliyah Umami; Dian Hayyu Rana Muna; Tias Dwiko Ningsih; Akhfan Mustofa Lutfi (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
The increase in cyber crime in Indonesia, especially data theft through phishing activities, prompted Bank BCA to launch an educational campaign entitled "Don't Know? Love No!" as part of their broader anti-fraud initiative, #AwasModus, on social media platforms against the rise of phishing phenomena. Educational ad "Don't Know? Love No!" encourages people to "slow down and reflect" before taking any action, especially when accessing or receiving messages from obscure and suspicious sources, such as links via SMS, email, messaging apps, or social media. The purpose of this study was to evaluate the effectiveness and impact of BCA's anti-fraud education campaigns, revealing their effect on public awareness, perception, and behavior change in response to widespread cyber threats. Through thorough analysis, the study aims to provide insight into the campaign's success in encouraging a more discreet and informed online society, contributing to broader efforts in reducing the risk of cybercrime and raising cyber security awareness in Indonesia.Keywords: Effectiveness, phishing, educational campaign, awareness, perception